Amphibians - Min, Pui Yong; Adi Shabrani, Mohammad Ridzuan; Veronica, Leah; Awang Ikhwan, Khairul; Indraneil, Das (UNIMAS Publisher and Natural History Publications (Borneo) Sdn Bhd, 2024)
The chapter enumerates the amphibian fauna of the Baleh region of Sarawak.